2007
DOI: 10.1001/archpedi.161.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Parental Compliance After Screening Social Development in Toddlers

Abstract: Objectives:To examine the prevalence of parents' compliance with follow-up measurements after their child tested positive at a screening to assess problems in social development, as well as to find demographic, screening-related, and child-specific factors associated with parental compliance.Design: Two-stage screening design.Setting: Utrecht, the Netherlands.Participants: A random population of 31 724 children were screened at well-baby clinics at age 14 to 15 months (screen 1). Three hundred sixty-four child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Dietz et al . found that most parents may delay compliance or be non‐compliant with discharge instructions that involved medically relevant advice . Arad et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietz et al . found that most parents may delay compliance or be non‐compliant with discharge instructions that involved medically relevant advice . Arad et al .…”
Section: Discussionmentioning
confidence: 99%
“…23 Dietz et al found that most parents may delay compliance or be non-compliant with discharge instructions that involved medically relevant advice. 24 Arad et al reported better parental compliance with neonatal discharge instructions when the content of the discharge memo was reinforced by a nurse before discharge, and both the nurse and mother signed the note. 25 Therefore, the current study provided discharge instructions orally and a recording form was handed to the parents to record the frequency of breast-feeding and diaper change; the nurse and parents were both required to sign the discharge document.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Glascoe (1999, 2003) and Tervo (2005) for example, found that parental concerns relate directly to their child’s wellbeing and development. Our prior work on population screening on autism spectrum disorders found that parental judgment about whether or not to comply with professional recommendations did reflect a rather accurate estimate of the severity of autistic symptoms of their child (Dietz et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, it remains possible that the parents of children who exhibited more severe developmental problems at age 2 were more inclined to react to our invitation for further assessment at the university lab after screening, which was also found in previous population screening studies [23,40]. This may have resulted in more developmentally challenged children with a false positive screen on the CESDD in the current sample compared to the general population.…”
Section: Limitationsmentioning
confidence: 71%
“…Yirmiya and Charman [40] concluded based on a review of both prospective and retrospective studies on early signs of ASD that we do not yet have sufficient insight in which of the early signs of ASD known to us are specific for ASD. In order to address this specificity question, they argued that we need data on children who do and do not continue to develop ASDs later on, after showing these early markers.…”
Section: Discussionmentioning
confidence: 96%